1994
DOI: 10.1111/j.1600-0714.1994.tb00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of fibroblast growth factor‐1 (FGF‐1) and FGF‐2 in oral squamous cell carcinoma (SCC)

Abstract: The localization of fibroblast growth factor-1 (FGF-1) and FGF-2 in human oral squamous cell carcinoma (SCC) was examined by immunohistochemical techniques using anti-FGF-1 and anti-FGF-2 monoclonal antibodies. Immunofluorescence staining of two oral SCC cell lines revealed that growing cancer cells were intensely positive for both FGF-1 and FGF-2, but confluent cells showed a faint immunostaining. In addition, two molecular mass species of FGF-1 (16 and 18 kDa) and one of FGF-2 (18 kDa) were identified by Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 28 publications
1
23
0
2
Order By: Relevance
“…Bansal et al (7) reported that the expression of FGF-1 is lower in breast cancer than in the normal human breast. Myoken et al (31) showed stronger expression of FGF-2 in oral squamous cell carcinomas than in normal tissue. Chow et al (14) demonstrated strong expression of FGF-1 and FGF-2 in normal liver cells, but weak expression of these factors in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bansal et al (7) reported that the expression of FGF-1 is lower in breast cancer than in the normal human breast. Myoken et al (31) showed stronger expression of FGF-2 in oral squamous cell carcinomas than in normal tissue. Chow et al (14) demonstrated strong expression of FGF-1 and FGF-2 in normal liver cells, but weak expression of these factors in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high expression levels of FGF2, a well-characterized angiogenic factor, but also FGF1, FGFR1 and FGFR2, have been linked to the progression of HNSCC. [22][23][24] However, a role for FGFR4 in this type of tumor has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Hox gene expression in chick embryos show that FGF modified the expressions of Hoxa2, b6-9, c6-9 and d9 (26)(27)(28)(29). The expression levels of FGF-1 nad FGF-2 are higher in SCC than in normal oral mucosa (30), and high affinity receptors for FGFs, FGFR2 and FGFR3, are highly expressed in dysplasia and SCC compared to those in normal mucosa (31). We showed here that the expression levels of HOXC6 were significantly higher in Sample code Histology T pN Location #11 C11 SCC 1 0 Tongue #14 C14 SCC 1 0 Tongue #20 C20 SCC 1 0 Tongue #25 C25 SCC 1 0 Tongue #1 C1 SCC 2 0 Tongue #3 C3 SCC 2 0 Tongue #5 C5 SCC 2 0 Tongue #10 C10 …”
Section: Discussionmentioning
confidence: 99%